Baikal endemic and Palearctic species of caddisflies (Trichoptera) build cases from microplastics - Karnaukhov, Dmitry Yu.; Lavnikova, Arina V.; Nepokrytykh, Anna V.; Zhdanov, Igor A.; Salovarov, Kirill V.; Guliguev, Artem T.; Osadchy, Bogdan V.; Biritskaya, Sofya A.; Ermolaeva, Yana K.; Maslennikova, Maria A.; Bukhaeva, Lidia B.; Golubets, Dmitry I.; et al. (Altai State University, 2024)
Pollution of freshwater ecosystems by microplastics is a serious problem. Many studies are related to the pelagic zone and the organisms living in it. However, benthic organisms are most susceptible to this problem in aquatic ecosystems. Benthic organisms can both consume microplastics and incorporate them into their cases. The last statement concerns caddisflies. In this study, cases and larvae of two caddisfly species were analyzed. The first species is endemic to Lake Baikal ( Baicalina thamastoides ), the second species is a Palearctic species ( Hydatophylax nigrovittatu s). Microplastic fragments were found in both species. However, we are the first to show that microplastic fragments can be embedded in cases in large numbers (from 10 to 38, with an average value of 20.56 ± 1.91 specimens/case in H. nigrovittatus ). For this species, there is a negative significant (p<0.05) correlation between the length of the larvae and the number of microplastic particles (fragments). In addition, mesoplastics with a length of more than 5 mm were found among the embedded particles.